Health risk reduction behaviors model for scavengers exposed to solid waste in municipal dump sites in Nakhon Ratchasima Province, Thailand - Thirarattanasunthon P; Siriwong W; Robson M; Borjan M (Dove Medical Press, 2012)
Phiman Thirarattanasunthon,1 Wattasit Siriwong,1,2 Mark Robson,2–4 Marija Borjan3 1College of Public Health Sciences, Chulalongkorn University, 2Thai Fogarty ITREOH Center, Chulalongkorn University, Bangkok, Thailand; 3School of Environmental and Biological Sciences, Rutgers University, New Brunswick, 4UMDNJ-School of Public Health, Piscataway, NJ, USAAbstract: The aim of this study was to evaluate the effect of comprehensive health risk protection behaviors, knowledge, attitudes, and practices among scavengers in open dump sites. A control group of 44 scavengers and an intervention group of 44 scavengers participated in this study. Interventions included the use of personal protective equipment, health protection training, and other measures. The analysis showed significant differences before and after the intervention program and also between the control and intervention groups. These observations suggest that further action should be taken to reduce adverse exposure during waste collection. To reduce health hazards to workers, dump site scavenging should be incorporated into the formal sector program. Solid waste and the management of municipal solid waste has become a human and environmental health issue and future research should look at constructing a sustainable model to help protect the health of scavengers and drive authorities to adopt safer management techniques.Keywords: scavenger, health risk reduction behaviors model (HRRBM), personal protective equipment (PPE), knowledge, attitude, and practice (KAP), waste health coordinator (WHC)